Women in the age group of 28 to 59 years old traveling alone or with other women - Gonçalves, Julia Pereira; Ghirotti, Gabryela Martins; Silva, Anna Letícia Januário; Batista, Sueli Soares dos Santos; Fernandez, Camila Collpy Gonzalez; Oliveira, Rodrigo Ribeiro de (Brazilian Journal of Production Engineering, 2022)
This work aims to analyze and compare the perception of women aged 28 to 59 years, observing the data collection carried out by the article "Brazilian women traveling alone and the means of accommodation", seeking to present the influence age group in travel perception and experiences. The compilation of testimonies showed that women do not stop making their trips, even with negative judgments or experiences, in addition to prioritizing moments that contribute to their independence and autonomy being developed. The focus groups showed positive results linked to the main research theme.
Keywords: Tourist Experiences; Women; Independent and Accompanied Travel; Tourism